Concrete-filled high-chromium stainless steel tube stub columns under combined compression and bending: experimental and numerical investigations - Zhong, Yukai (2023)
A new high-chromium grade EN 1.4420 stainless steel, which possesses higher material strength and better corrosion resistance but lower material price than the currently most commonly used grade EN 1.4301 stainless steel, has been recently developed, with a good potential in engineering practice. The present paper reports experimental and numerical investigations into the structural behaviour and resistance of concrete-filled high-chromium stainless steel tube (CFHSST) stub columns under combined compression and bending. The experimental investigation was conducted on twelve CFHSST stub column specimens fabricated from high-chromium grade EN 1.4420 stainless steel tubes with three cross-section sizes and concretes with two grades. The failure loads, mid-height lateral deflections, evolution of neutral axis and confinement effect were analysed and discussed. Numerical modelling was subsequently carried out, where finite element models were developed to simulate the test results and then employed to conduct parametric studies to generate further numerical data. The relevant design interaction curves, as set out in the European code, American specification and Australian/New Zealand standard, were assessed for their applicability to CFHSST stub columns under combined compression and bending, based on test and numerical data. The assessment results revealed that the European code and Australian/New Zealand standard provide overall accurate failure load predictions, while the American specification underestimates the failure loads for CFHSST stub columns under combined compression and bending, due to the conservative shape of the design interaction curve.